2016
DOI: 10.1590/0103-6440201600545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 15% Alcohol Dependence on Alveolar Bone Loss and TNF-α Secretion in Wistar Rats

Abstract: The aim of the present study was to evaluate the effect of 15% alcohol dependence on ligature-induced alveolar bone loss and TNF-α secretion in Wistar rats. Thirty-three male Wistar rats aged 45-60 days (mean weight=253 g) were randomly allocated test or control groups. Test group (n=18) received 15% alcohol as liquid intake and control group (n=15) received water during the experimental period. TNF-α was analyzed by ELISA assay in 11 animals per group. After 14 days of alcohol/water intake, alcohol dependency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Different protocols have tested the effect of ethanol exposure on periodontal diseases in animal models with distinct results [ 6 , 7 , 10 , 13 , 22 , 23 ]. The idea behind such studies comes from the demonstrated association between alcohol consumption, especially in high doses, with periodontal diseases in populational studies even in a longitudinal approach [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different protocols have tested the effect of ethanol exposure on periodontal diseases in animal models with distinct results [ 6 , 7 , 10 , 13 , 22 , 23 ]. The idea behind such studies comes from the demonstrated association between alcohol consumption, especially in high doses, with periodontal diseases in populational studies even in a longitudinal approach [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol harmful effects in the oral cavity seem to be proportional to the alcohol-exposure pattern [ 7 , 12 , 13 ]. Enzymatic induction, immune modifier, as well as cementum formation and osteoblast activity reduction have been suggested to alcohol-related oral cavity health disorders [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the specific regulatory mechanism of TNF- α on bone cells and the molecular mechanism in the pathogenesis of osteoporosis remain unclear. It has been reported that TNF- α plays a role in promoting alcohol-induced osteoporosis [ 69 , 70 ]. Given that necroptosis is a special type of necrosis mainly mediated by the stimulating death receptor of TNF- α [ 27 , 71 ], we examined the level of TNF- α in mouse serum and osteoblastic culture medium after EtOH intervention and Nec-1 treatment by ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…13 Different concentrations of alcoholic solutions have been used in several studies to simulate the alcoholic beverages consumed by humans. Wagner et al (2016) 14 used different concentrations of alcohol, defining low concentration as 5%, intermediate concentration as 13%, and high concentration as 20%. Another study also used 20% of alcohol as chronic consumption dose.…”
Section: Discussionmentioning
confidence: 99%